Surface topography effect on tribological performance of water-lubricated journal bearing under mixed-EHL regime. (1st December 2022) - Prajapati, Deepak K; Ramkumar, P
Abstract: Water-lubricated journal bearings (WLJB) are one of the important components of the stern tube shaft. Surface topography of WLJB is an important aspect in the design of stern tube shaft, and significantly affects the lubrication characteristics of WLJB. This work aims to investigate the effect of non-Gaussian surface topography on tribological performance of water-lubricated journal bearing (WLJB) under mixed-elastohydrodynamic lubrication (mixed-EHL) regime. The non-Gaussian flow factors, and a normalized Weibull probability density function is used to tackle the non-Gaussian roughness in hydrodynamic and asperity contact models respectively. From results, it is observed that skewness ( S sk ) significantly affects both asperity contact pressure and hydrodynamic pressure along circumferential direction of bearing. It is concluded that for skewness, S sk = −1 to 1, lambda ratio falls between 1 to 3. The relation between altitude angle and skewness is established. The effect of bearing length to diameter (L/D) ratio on lubrication performance of WLJB is also discussed in detail.